A systematic review of factors associated with outcome of psychological treatments for post-traumatic stress disorder. Issue 1 (31st December 2020) - Barawi, Kali S.; Lewis, Catrin; Simon, Natalie; Bisson, Jonathan I.
ABSTRACT: Objective: Psychological interventions for post-traumatic stress disorder (PTSD) are not always effective and can leave some individuals with enduring symptoms. Little is known about factors that are associated with better or worse treatment outcome. Our objective was to address this gap. Method: We undertook a systematic review following Cochrane Collaboration Guidelines. We included 126 randomized controlled trials (RCTs) of psychological interventions for PTSD and examined factors that were associated with treatment outcome, in terms of severity of PTSD symptoms post-treatment, and recovery or remission. Results: Associations were neither consistent nor strong. Two factors were associated with smaller reductions in severity of PTSD symptoms post-treatment: comorbid diagnosis of depression, and higher PTSD symptom severity at baseline assessment. Higher education, adherence to homework and experience of a more recent trauma were associated with better treatment outcome. Conclusion: Identifying and understanding why certain factors are associated with treatment outcome is vital to determine which individuals are most likely to benefit from particular treatments and to develop more effective treatments in the future. There is an urgent need for consistent and standardized reporting of factors associated with treatment outcome in all clinical trials.